Historical exposure to mercury among Norwegian dental personnel - Svendsen, Kristin; Syversen, Tore; Melø, Inger; Hilt, Bjørn (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVES ': 'Due to public concern in Scandinavian countries about the health situation of dental nurses, the Norwegian Ministry of Labor and Social Inclusion initiated a project to look at previous exposure to metallic mercury and its possible effects on dental personnel. The aims of this part of the study were to: (i) describe Norwegian dental personnel’s exposure to mercury during the last 50 years, (ii) develop a model for scoring that reflects the cumulative exposure on an individual basis, and (iii) relate the calculated score to earlier measured levels of mercury in urine. ' ' METHODS ': 'We obtained lists of previous and current dental employees in both the private and public sector and mailed them a questionnaire concerning their working conditions. We received a response from 655 dental nurses and 452 dentists. We also obtained urine mercury levels measured between 1970–1990 for 143 (22%) of the dental nurses and 130 (29%) of the dentists. ' ' RESULTS ': 'The results revealed a widespread exposure to mercury in both the individual exposure score and the measured mercury values in urine. For most respondents, however, the level of exposure to mercury seemed to be low. The use of copper amalgam, which is heated before it is applied, is of particular concern as a significant source of mercury exposure in dental personnel. ' ' CONCLUSION ': 'It seems evident that the exposure to mercury among dental personnel varies substantially; this is important to take into account when making exposure assessments for this group of workers.
Keywords: amalgam; copper amalgam; dental nurse; dental personnel; dentist; exposure; exposure assessment; historical exposure; mercury; Norway; nurse